2022
DOI: 10.1515/ntrev-2022-0479
|View full text |Cite
|
Sign up to set email alerts
|

Aptamer-functionalized chitosan-coated gold nanoparticle complex as a suitable targeted drug carrier for improved breast cancer treatment

Abstract: In the following research, we specifically assessed the feasibility of a novel AS-1411-chitosan (CS)-gold nanoparticle (AuNPs) delivery system to carry methotrexate (MTX) into the cancer cells. The designed system had a spherical shape with average size of 62 ± 2.4 nm, the zeta potential of −32.1 ± 1.4 mV, and released MTX in a controlled pH- and time-dependent manner. CS-AuNPs could successfully penetrate the breast cancer cells and release the therapeutic drug, and ultimately, be accumulated by the nucleolin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…Through further analysis, it was observed that the release of ZnPcS 4 from the AuNPs was faster at pH 5.4 compared to pH 7.4, suggesting that AuNPs could release PSs in a well-coordinated manner upon exposure to an acidic endo/lysosomal pH and intracellular reductive conditions in tumour cells. Similar observations were reported by Shahidi et al, who highlighted that AuNPs could effectively penetrate cancer cells and control the release of therapeutic drugs, thereby preventing unwanted drug leakage before reaching targeted tumour sites [ 38 ].…”
Section: Discussionsupporting
confidence: 83%
“…Through further analysis, it was observed that the release of ZnPcS 4 from the AuNPs was faster at pH 5.4 compared to pH 7.4, suggesting that AuNPs could release PSs in a well-coordinated manner upon exposure to an acidic endo/lysosomal pH and intracellular reductive conditions in tumour cells. Similar observations were reported by Shahidi et al, who highlighted that AuNPs could effectively penetrate cancer cells and control the release of therapeutic drugs, thereby preventing unwanted drug leakage before reaching targeted tumour sites [ 38 ].…”
Section: Discussionsupporting
confidence: 83%
“…This is in agreement with reports by Shahidi et al, who stated that AuNPs could improve the bioavailability and controlled release of drugs, thereby mitigating premature leakage of drugs in nontargeted regions. 33 The ZnPcS 4 dose optimization studies yielded an IC 50 concentration of 0.85 mM in monolayers and 12.73 mM in spheroids. Studies by Gunay et al, 2020 showed a 20-fold increase in the drug resistance of spheroids to PDT versus monolayers.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Chitosan coatings are also advantageous for the intracellular distribution of drugs by promoting the endosomal escape of encapsulated therapeutic cargo due to the proton sponge action of the cationic biopolymer [ 139 ]. Moreover, the presence of NH 2 groups together with OH groups ensures the high chemical reactivity of chitosan which can be easily modified with different functional molecules, such as stealth [ 169 , 170 , 171 ] or targeting [ 140 , 172 , 173 ] moieties.…”
Section: Functionalization Of Msns With Biopolymersmentioning
confidence: 99%